Determinants of African agricultural exports - Tadesse, Getaw; Badiane, Ousmane (International Food Policy Research Institute, 2018)
Chapter 5, by Getaw Tadesse and Ousmane Badiane, provides an in-depth examination of the determinants of African agricultural trade performance. The chapter reviews broad categories of trade determinants, including production capacity, the cost of trade, trade policies, domestic agricultural supports, and global market shocks. The chapter then develops a gravity model to assess the relative importance of determinants of African trade and of different trade constraints, discussing how these constraints have changed over time and vary across countries.